Mikrobiologiczne wskaźniki skażenia sanitarnego gleby w okolicy przeciekającego zbiornika bezodpływowego na nieczystości ciekłe = Microbiological indicators for sanitary soil contamination near leaking cesspool - Gajewska, Julitta; Wycech, Medard; Pladys, Wawrzyniec; Sysa, Paweł (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The main purpose of this thesis was to determine the microbiological indicators confirm that the phenomenon of leakages cesspool, contamination of nearby soil by municipal sewage. In the sewage samples and the soil were isolated and identified several species of bacteria, representing a potential health hazard: Escherichia coli, Enterococcus faecalis, Pseudomonas aeruginosa, Staphylococcus aureus, Clostridium difficile, Streptococcus uberis.
Keywords: ścieki komunalne; szambo; wskaźniki mikrobiologiczne; bakteriechorobotwórcze; gleba; municipal sewage; cesspool; microbiological indicators; pathogenic bacteria; soils